Incidence of Tuberculosis among HIV-infected patients receiving highly active antiretroviral therapy in Europe and North America. - Girardi, Enrico; Sabin, Caroline A; d'Arminio Monforte, Antonella; Hogg, Bob; Phillips, Andrew N; Gill, M John; Dabis, Francois; Reiss, Peter; Kirk, Ole; Bernasconi, Enos; Grabar, Sophie; Justice, Amy; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2005)
We obtained estimates of the incidence of tuberculosis (TB) among patients receiving HAART and identified determinants of the incidence.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Europe; Female; HIV Infections; Humans; Incidence; Male; North America; Tuberculosis